Evaluación de los pasivos ambientales de la empresa Probalsa cia.ltda. el Carmen-Manabí 2016. Diseño de un plan de acción para obtención la licencia ambiental - Jácome Sánchez, María Angélica (2017)
Companies that have within their activities the obligation to carry out an environmental compliance of the processes that are executed in this, must contemplate corrective activities established within the action plan and environmental management plan, which are designed to mitigate, reduce or eliminate the environmental impacts they generate. PROBALSA CIA.LTDA, because it is a company that has an obligatory environmental impact study that strictly complies with the environmental legislation, for this investigation an in situ inspection of the areas of reception and aserrio, drying area and boilers, Area of workshops and processes, Bending, brushing, sawing, quality control, shrinking and pressing of blocks, this route is carried out an identification of the sources of contamination through environmental monitoring and a analysis also of hazardous and non-hazardous waste management. dangerous. It was necessary to carry a matrix of environmental findings and Obligations in which it was contemplated control activities that were in the management plan since 2012 that the company obtained its environmental license N.-007-2012 of November 9, 2012 for The execution of the Project "Balsa Wood Processing Plant PROBALSA CIA LTDA, of the qualifications obtained after a documentary and technical verification of the Environmental Management Plan, License and legislation could be made the respective action plan for the company for the purpose That at the time they carry out the respective environmental audit and may have this tool that is important to present to the Control Entity that is the Ministry of the Environment through the Provincial Directorates of each Province.